2010
DOI: 10.1097/mph.0b013e3181ced25c
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal Strictures During Treatment for Acute Lymphoblastic Leukemia

Abstract: Esophageal stricture is a rare complication of paediatric cancer treatment that usually occurs after esophageal exposure to radiotherapy. We describe 4 cases of esophageal stricture during chemotherapy for acute lymphoblastic leukemia. All patients presented with refractory vomiting and were diagnosed with radiologic contrast studies. None of the patients had received radiotherapy. Esophageal candidiasis was seen in 2 patients but the remaining 2 patients had earlier systemic candidiasis. High-dose dexamethaso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…Injury to the esophagus results in severe fibrosis, mucosal atrophy, ischemic ulcerations and esophageal strictures [10, 11]. Isolated chemotherapy-induced esophageal strictures are a very rare entity and have only been described in the pediatric literature, specifically in the management of acute leukemias.…”
Section: Discussionmentioning
confidence: 99%
“…Injury to the esophagus results in severe fibrosis, mucosal atrophy, ischemic ulcerations and esophageal strictures [10, 11]. Isolated chemotherapy-induced esophageal strictures are a very rare entity and have only been described in the pediatric literature, specifically in the management of acute leukemias.…”
Section: Discussionmentioning
confidence: 99%
“…Strictures of the esophagus in children may result from caustic injury, congenital anomaly, chemoradiotherapy, inflammation, and chronic gastroesophageal reflux disease (GERD) [1][2][3][4]. Esophageal stricture occurring after prolonged GERD, known as peptic stricture (PS), can be identified in up to 15% of children with GERD and is a cause of immediate and long-term morbidity [5].…”
mentioning
confidence: 99%
“…Of the several thousand cases, included in these studies, only 2 cases of esophageal stricture were found in patients receiving chemotherapy alone. 4 , 5 In the adult population, only 2 patients have been previously identified who developed stricture during treatment with systemic chemotherapy. 2 , 3 In both of these cases, symptoms began within 3 weeks of initiation of systemic chemotherapy, as in our case.…”
Section: Discussionmentioning
confidence: 99%
“…2 , 3 In pediatric patients, it has been identified as a rare complication following induction therapy for acute leukemia. 4 …”
Section: Introductionmentioning
confidence: 99%